Evaluation of oxidative metabolism and oxidative DNA damage in patients with obsessive–compulsive disorder. Issue 2 (31st October 2015) - Alici, Demet; Bulbul, Feridun; Virit, Osman; Unal, Ahmet; Altindag, Abdurrahman; Alpak, Gokay; Alici, Hayri; Ermis, Berna; Orkmez, Mustafa; Taysi, Seyithan; Savas, Haluk
Abstract : Aims: There are limited published data about the role of oxidative stress in the pathophysiology of obsessive–compulsive disorder (OCD). In addition, oxidative stress and oxidative DNA damage have not been investigated together in OCD. In this study, we aimed to evaluate oxidative stress and oxidative DNA damage in patients with OCD. Methods: Forty‐two patients with OCD who were diagnosed in the Psychiatry Clinic of Gaziantep University and 38 healthy volunteers were enrolled in the study. Serum 8‐hydroxideoxiguanosine (8‐OHdG), total antioxidant status, total oxidant status evaluation and oxidative stress index calculation were conducted in Gaziantep University Biochemical Laboratory. Results: There were no significant differences in the total antioxidant status, total oxidant status and oxidative stress index levels between the patients and control group. However, 8‐OHdG levels were significantly higher in OCD patients than controls ( P  = 0.022). In addition, 8‐OHdG levels were significantly lower in patients who took treatment than in patients who were newly diagnosed ( P  = 0.016). Conclusions: In our study, we found that oxidative DNA damage increased in OCD patients even though oxidative stress was normal. In addition, DNA damage was lower in patients who were treated compared to those without treatment.